Coal Seam Roof: Lithology and Influence on the Enrichment of Coalbed Methane - He, Yunlan; Wang, Xikai; Sun, Hongjie; Xing, Zhenguo; Chong, Shan; Xu, Dongjing; Feng, Feisheng (Earth Sciences Research Journal, 2019)
To identify the lithology of coal seam roof and explore the influence of these roofs on the enrichment of coalbed methane, low-frequency rock petrophysics experiments, seismic analyses and gas-bearing trend analyses were performed. The results show that the sound wave propagation speed in rock at seismic frequencies was lower than that at ultrasound frequencies. Additionally, the P-wave velocities of gritstone, fine sandstone, argillaceous siltstone and mudstone were 1,651 m/s, 2,840 m/s, 3,191 m/s and 4,214 m/s, respectively. The surface properties of the coal seam roofs were extracted through 3D seismic wave impedance inversion. The theoretical P-wave impedance was calculated after the tested P-wave velocity was determined. By matching the theoretical P-wave impedance of the four types of rocks with that of the coal seam roofs, we identified the lithology of the roofs. By analyzing known borehole data, we found that the identified lithology was consistent with that revealed by the data. By comparing and analyzing the coal seam roof lithology and the gas-bearing trends in the study area, we discovered that the coal seam roof lithology was related to the enrichment of coalbed methane. In the study area, areas with high gas contents mainly coincided with roof zones composed of mudstone and argillaceous siltstone, and those with low gas contents were mainly associated with fine sandstone roof areas. Thus, highly compact areas of coal seam roof are favorable for the formation and preservation of coalbed methane.